Hotel Human Resources Policy In Maintaining Employee Performance During The 19 Covid Pandemic - Parantika, Asep; Yubilika, Maria Josephine; Rini, Nuryadina Augus (Jurnal Penelitian Pariwisata, 2021)
During the COVID-19 pandemic, the tourism and hospitality sector was the sector that suffered the most losses. Some hotels began to bankrupt, so they had to prepare various strategies to survive. One of the plans is to lay off some employees, leave them unpaid, and terminate their employment with an honorary employee. One of the rules created was Large-Scale Social Restriction. The management hotel also implements PSBB policies and creates new regulations for its workers to make the hotel exists. The goals of this study are (1) to know HRD policies in maintaining employee performance before and after the COVID-19 pandemic; (2) to find out the effect of the new policies created by HRD on their employees during the COVID-19 pandemic; (3) to find out the hotel targets after the COVID-19 pandemic ends. Researchers used qualitative research methods with a descriptive approach. Data collection techniques used were interviews with HRD managers of four to five-star hotels and journal reviews. The results show that HRD makes rules by implementing health protocols. HRD also minimizes expenses by laying off employees with low levels of performance, using an outsourced workforce, and reducing electricity and water consumption on some floors that are not functioning or temporarily closed. During this pandemic, employees need to work multitasking so that the hotel provides training both online and offline. The hotel management hopes that after this pandemic ends, the hotel can bounce back with the occupancy rate and restaurant visitors increasing, guests can hold large-scale events at the hotel. Keywords: COVID-19, Employee Performance, HRD Policy